2015
DOI: 10.1371/journal.pone.0142913
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Mental Adjustment in the Relationship between Perceived Stress and Depressive Symptoms in Hematological Cancer Patients: A Cross-Sectional Study

Abstract: BackgroundDepression is a particularly common psychological disorder that affects cancer patients. Diagnosed with hematological malignancies constitute a serious unpredictable and uncontrollable medical stress situation and patients are susceptible to suffer from depressive symptoms. The aims of the study were to explore the correlation between perceived stress and depressive symptoms in patients with hematological malignancies, and assess the mediating role of mental adjustment between these variables.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 40 publications
(39 reference statements)
1
25
1
Order By: Relevance
“…Interestingly, we found that perceived stress served as a mediator in the link between SFG spontaneous activity and depressive symptoms. Behaviorally, the association of perceived stress with depressive symptoms has been well established in previous investigations (Bay & Donders, 2008;Bergdahl & Bergdahl, 2002;Chao, 2014;Chen et al, 2017;Eisenbarth, 2012;Farabaugh et al, 2004;Gao et al, 2009;Ghorbani et al, 2008;Hewitt et al, 1992;Kuiper et al, 1986;Lee et al, 2013;Li et al, 2015;Lorenzo-Blanco & Unger, 2015;Martin et al, 1995;Rosal et al, 1997;Tsai & Chang, 2016;Williams et al, 2017). This association was replicated in the current sample (r = .53, p < .001).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, we found that perceived stress served as a mediator in the link between SFG spontaneous activity and depressive symptoms. Behaviorally, the association of perceived stress with depressive symptoms has been well established in previous investigations (Bay & Donders, 2008;Bergdahl & Bergdahl, 2002;Chao, 2014;Chen et al, 2017;Eisenbarth, 2012;Farabaugh et al, 2004;Gao et al, 2009;Ghorbani et al, 2008;Hewitt et al, 1992;Kuiper et al, 1986;Lee et al, 2013;Li et al, 2015;Lorenzo-Blanco & Unger, 2015;Martin et al, 1995;Rosal et al, 1997;Tsai & Chang, 2016;Williams et al, 2017). This association was replicated in the current sample (r = .53, p < .001).…”
Section: Discussionsupporting
confidence: 84%
“…A wealth of previous studies have suggested that perceived stress plays an essential role in the onset and development of depressive symptoms among different populations (Bay & Donders, 2008;Bergdahl & Bergdahl, 2002;Chao, 2014;Chen, Peng, Ma, & Dong, 2017;Eisenbarth, 2012;Farabaugh et al, 2004;Gao, Chan, & Mao, 2009;Ghorbani, Krauss, Watson, & LeBreton, 2008;Hewitt, Flett, & Mosher, 1992;Kuiper, Olinger, & Lyons, 1986;Lee, Joo, & Choi, 2013;Li, Yang, Zhang, Yao, & Liu, 2015;Lorenzo-Blanco & Unger, 2015;Martin, Kazarian, & Breiter, 1995;Rosal et al, 1997;Tsai & Chang, 2016;Williams, Turner-Henson, Davis, & Soistmann, 2017). For example, a number of crosssectional studies have revealed a positive association of perceived stress with depressive symptoms among healthy individuals (Bergdahl & Bergdahl, 2002;Chen et al, 2017;Eisenbarth, 2012;Gao et al, 2009;Ghorbani et al, 2008;Kuiper et al, 1986;Lee et al, 2013;Williams et al, 2017) and clinical patients (Bay & Donders, 2008;Farabaugh et al, 2004;Hewitt et al, 1992;Li et al, 2015;Martin et al, 1995). Furthermore, several longitudinal studies have shown that perceived stress can predict subsequent depressive symptoms in different populations (Chao, 2014;Lorenzo-Blanco & Unger, 2015;Rosal et al, 1997;Tsai &a...…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of logistic regression analysis, perceived stress was associated with both anxiety and depressive symptoms. Other researches [6,51]suggested that the perceived stress impacted the depressive and anxiety symptoms of cancer patients through their mental adjustment. It could be explained by the fact that a cancer diagnosis is a stressful event for most individuals, and patients experience mental stress such as worries about prognosis and treatments, disruption of daily functions and survival time [52].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of logistic regression analysis, perceived stress was associated with both anxiety and depressive symptoms. Other researches [6,46]suggested that the perceived stress impacted the depressive and anxiety symptoms of cancer patients through their mental adjustment. It could be explained by the fact that a cancer diagnosis is a stressful event for most individuals, and patients experience mental stress such as worries about prognosis and treatments, disruption of daily functions and survival time [47].…”
Section: Discussionmentioning
confidence: 99%